NON-PECUNIARY DAMAGE AS AN EXPRESSION OF THE PROTECTION OF SOCIAL VALUES - Arsenijević, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
In the paper the author pays attention to the development of non-pecuniary damage and the accepted concepts of the non-pecuniary damage, observing them through the prism of the protection of social values. Contrary to the protection of material goods in the form of the obligation to compensate for material damage, the protection of intangible goods has always inspired the opposed opinions. In the earlier stages of the development of law, the principle of talion allowed respect for the physical integrity of a person, but it did not ensure the compensation of the injured party (except in the form of a feeling of satisfaction of revenge), but rather the punishment of the harmer. Injury to the psychological (emotional, internal) sphere of a person’s being, on the other hand, used not to be a protected legal interest because the nature of damages, as believed, was not capable of compensating for this injury. The development of legal thought provided a firm foothold for the protection of the intangible interests of (wo)man. The next step involved determining the scope of the concept of non-pecuniary damage. In the collision of subjective and objective conceptions of non-pecuniary damage, legislators followed one of the approaches or a mixed concept. Finally, the acceptance of a certain concept creates a path for protection of social values that the legal system emphasize through the non-pecuniary damage. The Serbian Act of Obligations defines non-pecuniary damage as inflicted physical pain, psychological pain or fear (subjective conception), which arise as a result of quantifiable injuries to the intangible interests of a person (harm caused to body, honor or reputation, loss of a loved one, etc.). The detected shortcomings of this concept inspired the Croatian and Montenegrin legislators to deviate from the common source. The latter examples follow the Principles of European tort law (PETL). Although both conceptions seek to embrace, essentially, the same intangible interests of (wo)man, the different approaches consequently lead to different scopes of protection. The draft of the Civil Code of the Republic of Serbia contains a proposal of a mixed concept, defining non-pecuniary damage as a violation of personal rights and as the infliction of physical or psychological pain. Achieving legal certainty requires a cautious approach in proposing and implementing changes in domestic tort law.